Measurement of the diffractive structure functionF 2 D(4) at HERA - Chwastowski, J.; Figiel, J.; Klimek, K.; Zawiejski, L.; Bednarek, B.; Bukowy, M.; Jelen, K.; Suszycki, L.; Kotanski, A.; Antonioli, P.; Koch, W.; Manczak, O.; et al. (The European Physical Journal C, 1998)
This paper presents the first analysis of diffractive photon dissociation events in deep inelastic positron-proton scattering at HERA in which the proton in the final state is detected and its momentum measured. The events are selected by requiring a scattered proton in the ZEUS leading proton spectrometer (LPS) with χL > 0.97, where xL is the fraction of the incoming proton beam momentum carried by the scattered proton. The use of the LPS significantly reduces the contamination from events with diffractive dissociation of the proton into low mass states and allows a direct measurement of t, the square of the four-momentum exchanged at the proton vertex. The dependence of the cross section ont is measured in the interval 0.073 < |t| < 0.4 GeV2 and is found to be described by an exponential shape with the slope parameterb = 7.2 ± 1.1(stat.)−0.9+0.7(syst.) GeV−2. The diffractive structure function FD (4) is presented as 0.9 a function of χH ≃ 1 − χL and β, the momentum fraction of the struck quark with respect to χH, and averaged over thet interval 0.073 < |t′ < 0.4 GeV2 and the photon virtuality range 5 <Q2 < 20 GeV2. In the kinematic range 4 × 104 < χp < 0.03 and 0.015 < β < 0.5, the χp dependence ofFD(4) is fitted with a form (1/χp)α , yieldinga − 1.00 ± 0.09 (stat.)−0.05+0.11(syst.). Upon integration overL, the structure functionF2D(3) is determined in a kinematic range extending to higher χp and lower β compared to our previous analysis; the results are discussed within the framework of Regge theory.